Effect of SC 38249, a Novel Substituted Imidazole, on Platelet Aggregation In Vitro and In Vivo - Lad, N; Honey, A C; Lunt, D O; Booth, R F G; Westwick, J; Manley, P W; Tuffin, D P (Thrombosis and Haemostasis, 1988)
SC 38249 ((RS)-l-(2,3-bis-[(4-methoxyphenyl)methoxy] propyl)-lH-imidazole) caused dose-related inhibition of collagen- induced thromboxane A2 formation in human platelet rich plasma (IC50: 9.9 ± 1.0 μM) accompanied by a dose-dependent increase in plasma PGE2. Broad inhibitory activity was evident against human platelet aggregatory and secretory responses in vitro.IC50 values of 11.9 ± 1.9 μM (0.64 mM arachidonic acid), 18.3 ± 3.8 μM (0.5 μg ml−-1collagen) and 37.6 ± 6.1 μM (25 nM Paf-acether) were obtained against maximum increase in PRP light transmission achieved by each agonist. Although less potent, SC 38249 retained significant inhibitory activity against PRP responses induced by a higher (3.0 μg ml−-1) concentration of collagen (IC50: 272.5 ± 24.6 μM), and against Paf-acether-induced responses in PRP pre-treated with 10 μM indomethacin (I.C.50: 192.0 ± 16.1 μM).Experimental animal studies confirmed the in vitroanti-aggregatory efficacy of SC 38249, since significant inhibitory activity was observed against Paf-acether and ADP-induced responses in dog PRP ex vivo,anti-Forssman antibody-induced thrombocytopoenia in anaesthetized guinea pigs, and collagen-induced intravascular aggregation in anaesthetized rabbits. Thus, SC 38249 is a novel thromboxane synthase inhibitor which possesses interesting anti-aggregatory properties which cannot wholly be attributed to prevention of platelet thromboxane A2 formation.
Keywords: SC 38249; Thromboxane synthase inhibitor; Anti-aggregatory properties